Analysis of the Situation, Improvement of the Offer and Creation of the Development Strategy of the Camp Zagreb Destination 2024 - 2030 - Burušić, Brigita; Tanasić, Aleksandar (Program održivog razvoja Svete Nedelje, Jastrebarskog i Samobora, 2024)
This paper analyses the current state of the 'Camp Zagreb' campsite in Rakitje near Sveta Nedelja. Based on the conducted analysis, the goal was to create an example of a development strategy that could serve as a foundation for the further growth of the campsite. This paper covers fundamental concepts of camping and camping tourism and its history. The presented location has been in continuous operation since 2014 and is currently undergoing expansion. The situational analysis included examining the issues at the site, potential limitations, opportunities, and aspirations, which would later guide the proposed solutions. The paper introduces Sveta Nedelja as the town where the site is located and upon whose development it somewhat depends. Additionally, the paper describes Camp Zagreb and its offerings and identifies challenges. Finally, a potential strategy for the site's development and the author's opinion on the best option to address critical issues are outlined. A vision for the campsite by 2030 and key strategic priorities are also presented. Therefore, this paper's primary goal was to analyse the campsite and its surroundings and explore potential opportunities for further development.